2021
DOI: 10.1101/2021.01.12.426467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dimensionality reduction by UMAP reinforces sample heterogeneity analysis in bulk transcriptomic data

Abstract: Transcriptome profiling and differential gene expression constitute a ubiquitous tool in biomedical research and clinical application. Linear dimensionality reduction methods especially principal component analysis (PCA) are widely used in detecting sample-to-sample heterogeneity in bulk transcriptomic datasets so that appropriate analytic methods can be used to correct batch effects, remove outliers and distinguish subgroups. In response to the challenge in analysing transcriptomic datasets with large sample … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 65 publications
(72 reference statements)
0
21
0
Order By: Relevance
“…Specifically, UMAP first constructs a k‐nearest neighbour (kNN) graph to approximate the manifold structure of data, then embeds the kNN graph to two‐dimensional space to visualize the data (Figure 4B). UMAP has been shown to have a better capacity at maintaining local information as well as global structure in analyzing datasets for scRNA‐seq 70 …”
Section: Improvement Of the Mining Of Omics Data By New Analytic Methods Including Machine Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, UMAP first constructs a k‐nearest neighbour (kNN) graph to approximate the manifold structure of data, then embeds the kNN graph to two‐dimensional space to visualize the data (Figure 4B). UMAP has been shown to have a better capacity at maintaining local information as well as global structure in analyzing datasets for scRNA‐seq 70 …”
Section: Improvement Of the Mining Of Omics Data By New Analytic Methods Including Machine Learningmentioning
confidence: 99%
“…UMAP has been shown to have a better capacity at maintaining local information as well as global structure in analyzing datasets for scRNA-seq. 70 A recent study systemically compared UMAP with other mainstream methods for dimensionality reduction including PCA and demonstrated that UMAP was superior to PCA for clustering accuracy, neighbour information preserving and feature separating. 70 In this study, a data set consisting of longitudinal transcriptome profiles of 65 SLE patients and 20 HCs was analyzed.…”
Section: Improvement Of the Mining Of Omics Data By New Analytic Methods Including Machine Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the topic words visually, we use the Uniform Manifold Approximation and Projection (UMAP), an effective [59] and efficient [3] dimensionality reduction method, to reduce the dimensionality of the GloVe embeddings. This method works by finding lowdimensional projections of the data that preserves their topological structures in highdimensional space as much as possible [39].…”
Section: Identifying Over-represented Termsmentioning
confidence: 99%
“…Highly efficient implementations of t-SNE 30 and UMAP 31 have been made available recently (late 2018), and the latter has seen widespread used in many application domains. [32][33][34][35][36][37] Within the context of these tools, it is interesting to consider their efficacy for: 1) identifying collective variables for small molecule reactions in the condensed phase (where solvent participates in the reaction coordinates), and subsequently 2) their ability to elucidate the importance of solvent degrees of freedom within the reduced energy landscape framework.…”
Section: Introductionmentioning
confidence: 99%